2016
DOI: 10.1093/swr/svv047
|View full text |Cite
|
Sign up to set email alerts
|

Tangible Needs and External Stressors Faced by Chinese American Families with a Member Having Schizophrenia

Abstract: This article examines the tangible needs and external stressors experienced by Chinese American families with a member living with schizophrenia, in the context of a six-month pilot study of family psychoeducation. Therapists' notes from 117 family and group sessions were analyzed. The families expressed concerns regarding housing, finance, work, study, and the shortage of bilingual psychosocial services. Interacting with government offices and social services agencies caused anxiety and frustration, partly du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…By learning to accept the situation and by implementing alternative coping methods, family caregivers’ mental health can be improved. Not accepting the behaviour of a mentally ill relative may cause additional stress not only to the family caregiver but also to the relative as well (Kung 2016). Some family caregivers said they made efforts to accommodate and accept their relative living with mental illness.…”
Section: Resultsmentioning
confidence: 99%
“…By learning to accept the situation and by implementing alternative coping methods, family caregivers’ mental health can be improved. Not accepting the behaviour of a mentally ill relative may cause additional stress not only to the family caregiver but also to the relative as well (Kung 2016). Some family caregivers said they made efforts to accommodate and accept their relative living with mental illness.…”
Section: Resultsmentioning
confidence: 99%
“…Diverse negative effects on carers include disrupted relationships, psychological distress, and financial difficulties (Kung 2016a;Lin et al 2018). Researchers have developed the notion of caregiving burden to capture these negative effects experienced by families.…”
Section: Impact Of Mental Illness On Families and Carersmentioning
confidence: 99%
“…Most carers did not choose this role for themselves but rather acted out of a sense of responsibility they get involved in the care for their ill relatives (Lawn and Mcmahon 2014). Many, however, accepted the role positively and demonstrated devotion to their loved ones (Kung 2016a;Thorning and Dixon 2016). Moreover, caregiving could sometimes be reciprocal as carers also received emotional and practical help from the family members for whom they cared (Chen and Greenberg 2004;Coldwell et al 2011).…”
Section: Positive Impactmentioning
confidence: 99%
“…Alleviating patients' psychiatric symptoms and psychological distress among caregivers are both valid concerns for mental health professionals (Lefley, 2009). Immigrants have a higher risk of schizophrenia compared to native-born individuals (Werbeloff et al, 2012), and immigrant caregivers of patients with schizophrenia undergo high levels of stress, burden, and internalised stigma (Kung, 2016a(Kung, , 2016bYang et al, 2014). Although there are no specific data regarding the prevalence of schizophrenia among Chinese Americans, such disorder within this majority immigrant population could be sizeable, based on the National Latino and Asian American Study which reported that 1.12 per cent of Asians were found to have psychotic experiences (Oh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%